PERAN MOTIVASI INTRINSIK DAN KETERLIBATAN KERJA YANG MEMEDIASI LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - Rohadatul Aisy Hanifah; Sidiq Permono Nugroho (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2024)
The purpose of this study was to analyze the effect of work environment on employee performance with intrinsic motivation and work involvement as an intervening medium at Kpp Pratama Semarang. The method used in this research is a quantitative method with 165 respondents, data collection in this study using a questionnaire. The data was obtained directly by the researcher through a questionnaire distributed to respondents, namely all employees of KPP Pratama Semarang. The sampling technique in this study is nonprobability sampling technique with purposive sampling method, the data used is primary data obtained through respondents' answers using a type of interview or closed questionnaire. The data analysis technique used in this study uses Partial Least Square (PLS) using the help of SMARTPLS Software. PLS-SEM analysis consists of two Outer model and Inner model. The results of this study indicate that the work environment has no effect on employee performance, work involvement and intrinsic motivation mediate the relationship between the work environment and employee performance.